Political Change Patterns of The Mataraman Society in Kediri: (Study of Political Sociology in Mataraman Kediri on Election of Political Parties) - Taufik Alamin; Darsono Wisadirana; Sanggar Kanto; Hilmy Mochtar; Sholih Mu'adi; Mardiyono Mardiyono (Journal of Development Research, 2020)
Social political change in society is one of the social facts that cannot be avoided. The socio-political phenomenon is a dynamic and tentative situation. This research is oriented towards analyzing the political changes of the Mataraman society in Kediri. The method used is qualitative descriptive approach with case studies. Primary and secondary data sources are obtained from interviews and references, supporting documents are used as a tool in describing the subject of the study. The results showed that the political dynamics in Kediri influenced the changes in political patterns of the Mataraman society in Kediri. The powerful socio-culture of Matraman society is not faded with the changes in political choices occurred.